Crosstalk between autophagy and insulin resistance: evidence from different tissues - Asie Sadeghi; Maryam Niknam; Mohammad Amin Momeni-Moghaddam; Maryam Shabani; Hamid Aria; Alireza Bastin; Maryam Teimouri; Reza Meshkani; Hamed Akbari (European Journal of Medical Research, 2023)
Abstract Insulin is a critical hormone that promotes energy storage in various tissues, as well as anabolic functions. Insulin resistance significantly reduces these responses, resulting in pathological conditions, such as obesity and type 2 diabetes mellitus (T2DM). The management of insulin resistance requires better knowledge of its pathophysiological mechanisms to prevent secondary complications, such as cardiovascular diseases (CVDs). Recent evidence regarding the etiological mechanisms behind insulin resistance emphasizes the role of energy imbalance and neurohormonal dysregulation, both of which are closely regulated by autophagy. Autophagy is a conserved process that maintains homeostasis in cells. Accordingly, autophagy abnormalities have been linked to a variety of metabolic disorders, including insulin resistance, T2DM, obesity, and CVDs. Thus, there may be a link between autophagy and insulin resistance. Therefore, the interaction between autophagy and insulin function will be examined in this review, particularly in insulin-responsive tissues, such as adipose tissue, liver, and skeletal muscle.